CORRELATION OF STRESS LEVEL WITH HYPERTENSION IN THE ELDERLY - Kamsari, Kamsari; Dede Husnaniyah, Dede Husnaniyah; Riyanto, Riyanto; Evi Malita, Evi Malita (Universitas Islam Negeri Alauddin Makassar, 2022)
Stress is one of the factors of hypertension. Stress can cause blood pressure to increase intermittently through sympathetic nerve activity. It can cause hypertension. Purpose: the research aims to determine the correlation between stress levels and the incidence of hypertension in the elderly in the working area in Sukra Health Service Cente, Indramayu. This research is quantitative research with a correlational. A sample of 95 elderly was determined using a simple random sampling technique. The instruments in this study were the part of depression anxiety stress scale (DASS 42) questionnaire and the sphygmomanometer. Univariate analysis in this study describes the level of stress and the incidence of hypertension in the elderly. Bivariate analysis in this study is the relationship between stress levels and the incidence of hypertension in the elderly. The data were analyzed using the Pearson chi-square test. The results of this study indicate that respondents who do not experience stress or are expected are 88 (92.6%), while respondents who have hypertension are 50 (52.6%). The bivariate analysis showed p-value = 0.080 (α = 0.05). The conclusion is that there is no relationship between stress levels and the incidence of hypertension in the elderly. Suggestions for health services to improve health services for the elderly such as health centers for the elderly so that hypertension in the elderly can be controlled. Keywords: Hypertension, Elderly, Stress